Dynamics of entanglement and quantum discord in the Tavis-Cummings model (2016)
We revisit the problem of the dynamics of quantum correlations in the Tavis-Cummings model. Our results show that the dynamics of entanglement and quantum discord are far from being trivial or intuitive. We find states with the same entanglement but different discord and states where the two quantifiers give opposite information about correlations at a certain time. We furthermore show that many of the dynamical features of quantum discord attributed to dissipation are already present in the exact framework and are due to the characteristic quantum nonlinearity of the model and to the choice of initial conditions. Through a comprehensive analysis of pure and mixed initial conditions, we find a fascinating range of phenomena that can be used for experimental purposes. We propose an experiment called quantum discord gates where for given pure initial condition discord is zero or non-zero depending on the number of photons in the cavity. Given the marginal character of states with zero discord this result is not only completely counterintuitive but is also useful as a way to count photons.